High Efficiency Secondary Somatic Embryogenesis in Hovenia dulcis Thunb. through Solid and Liquid Cultures. (29th May 2013) - Yang, Jingli; Wu, Songquan; Li, Chenghao
Abstract : Embryogenic callus was obtained from mature seed explants on medium supplemented with 2, 4-dichlorophenoxyacetic acid. Primary somatic embryos (SEs) can only develop into abnormal plants. Well-developed SEs could be obtained through secondary somatic embryogenesis both in solid and liquid cultures. Temperature strongly affected induction frequency of secondary embryogenesis. Relatively high temperature (30 ∘ C ) and germinated SEs explants were effective for induction of secondary somatic embryos, and low temperature (20 ∘ C ) was more suitable for further embryo development, plantlet conversion, and transplant survival. Somatic embryos formed on agar medium had larger cotyledons than those of embryos formed in liquid medium. Supplementing 0.1 mg L − 1 6-benzyladenine (BA) was effective for plant conversion; the rate of plant conversion was 43.3% in somatic embryos from solid culture and 36.5% in embryos from liquid culture. In vitro plants were successfully acclimatized in the greenhouse. The protocol established in this study will be helpful for large-scale vegetative propagation of this medicinal tree.